Aid on Demand: African Leaders and the Geography of China's Foreign Assistance - Axel Dreher; Andreas Fuchs; Roland Hodler; Bradley C. Parks; Paul A. Raschky; Michael J. Tierney (Center for Economic Studies and ifo Institute (CESifo), 2015)
This article investigates whether China's foreign aid is particularly prone to political capture by political leaders of aid-receiving countries. Specifically, we examine whether more Chinese aid is allocated to the political leaders' birth regions and regions populated by the ethnic group to which the leader belongs, controlling for indicators of need and various fixed effects. We have collected data on 117 African leaders' birthplaces and ethnic groups and geocoded 1,650 Chinese development finance projects across 3,097 physical locations committed to Africa over the 2000-2012 period. Our econometric results show that current political leaders' birth regions receive substantially larger financial ows from China than other regions. On the contrary, when we replicate the analysis for the World Bank, our regressions with region-fixed effects show no evidence of such favoritism. For Chinese and World Bank aid alike, we also find no evidence that African leaders direct more aid to areas populated by groups who share their ethnicity, when controlling for region-fixed effects.
Keywords: D73; F35; P33; R11; 330; foreign aid; favoritism; aid allocation; Africa; China; official development assistance; georeferenced data; spatial analysis